(untitled) - Biggs, Douglas (Historica Olomucensia, 2024)
Anne of Bohemia, queen of Richard II from 1381 until her death in 1394, is often seen as "docile" or "demure" by British medievalists. Even though few records relating to Anne survive in the National Archives in London, through an investigation of her affinity one can gain a measure of Anne's political place in Richard II's reign. This article considers the composition of her affinity, the military roles played by her retainers, and the presence of her retainers in Parliament. What emerges from this brief discussion is a portrait of Anne's affinity starting from the group of men and women who accompanied her from the Empire to London in 1381, then the additional Englishmen and women chosen for her by her mother-in-law, and finally to a group of men and women who were drawn to Anne by her own abilities and skills. What emerges from this short study is a conclusion that Anne of Bohemia was a skillful manager of people and a powerful political patron. Men and women sought her as their lady and patron and careers were made in her service.
Keywords: Anne of Bohemia; Richard II; Parliament; Affinity; Retaining; Joan of Kent